2016
DOI: 10.1016/j.jtho.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lymph Node Ratio to Replace the pN Categories System of Classification of the TNM System in Esophageal Squamous Cell Carcinoma

Abstract: LNR can supplement the pN categorization system for more effective evaluation of prognosis. But the modified staging system based on LNR has a poor clinical practical value for patients with ESCC compared with the current TNM system and is not superior to AJCC pN staging for ESCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 31 publications
(52 reference statements)
5
47
0
Order By: Relevance
“…The ratio of metastatic lymph nodes is affected by the number of examined LNs. Additionally, this study found that the lymph node ratio is an independent predictor of survival in patients undergoing esophagectomy for ESCC, which was consistent with the prior literature 3,4,18 . Lymph node ratio may compensate for de ciencies in the AJCC nodal categories, and combining the lymph node ratio and AJCC nodal categories may more accurately predict survival than the current staging system 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The ratio of metastatic lymph nodes is affected by the number of examined LNs. Additionally, this study found that the lymph node ratio is an independent predictor of survival in patients undergoing esophagectomy for ESCC, which was consistent with the prior literature 3,4,18 . Lymph node ratio may compensate for de ciencies in the AJCC nodal categories, and combining the lymph node ratio and AJCC nodal categories may more accurately predict survival than the current staging system 19 .…”
Section: Discussionsupporting
confidence: 92%
“…The inclusion criteria were as follows: ESCC, R0 resection, no other malignant tumor, no lymph node metastasis, no distant metastasis, no radiotherapy and/or chemotherapy before or after surgery. Follow-up was conducted as described previously [ 26 ]. The research agreement was signed according to the guidelines formulated by the Declaration of Helsinki after the approval of the Ethics Committee of the Third People's Hospital of Yanchen.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the number of nodes dissected, the extent of mediastinal lymph node dissection is even more important to the outcome of esophagectomy (54)(55)(56). As mentioned earlier, regional lymph node identification and dissection should be based on the understanding of the anatomy of esophageal lymphatic drainage in all 9 stations of mediastinal lymph nodes as defined in the current consensus, and they should be dissected systemically in a radical esophagectomy.…”
Section: Extent Of Thoracic Lymphadenectomy In Radical Surgery For Esmentioning
confidence: 99%